The Role of Domestic Investment and Human Capital in Economic Performance: Does the Monetary and Fiscal Policy Mix Matter? - Ramadhani, Muhammad Akbar; Basri; Atkiyan, Fahrul Hudatil (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
This study examines the impact of domestic investment and human capital on three key regional economic development challenges—income inequality, poverty, and unemployment—across ten provinces in Sumatra during the period 2010–2023. Using a panel data regression model and moderation regression analysis (MRA), the research also investigates the moderating role of fiscal and monetary policy mixes. The results indicate that domestic investment is significantly and negatively associated with income inequality and unemployment; however, its effect on poverty is statistically insignificant. Human capital, proxied by the Human Development Index (HDI), shows a significant negative effect on both income inequality and poverty, but a significant positive effect on unemployment. Monetary policy, proxied by the BI rate, has a significant positive impact on income inequality and unemployment, with no significant influence on poverty. Additionally, monetary policy is found to weaken the effect of domestic investment in reducing both income inequality and unemployment. Fiscal policy, represented by government spending, has a significant negative effect on poverty and a significant positive effect on unemployment, while showing no significant impact on income inequality. Moreover, fiscal policy strengthens the effect of HDI in reducing inequality and poverty, while simultaneously weakening its effect in increasing unemployment.